Photoreduction Kinetics of Sodium Tetrachloroaurate under Synchrotron Soft X-ray Exposure - Fong, Y.; Visser, B.; Gascooke, J.; Cowie, B.; Thomsen, L.; Metha, G.; Buntine, Mark; Harris, H. (American Chemical Society, 2011)
We report on the time evolution of the sodium tetrachloroaurate (NaAuCl4) chemical properties as a function of soft X-ray exposure in a dried sample on a silicon surface using X-ray photoelectron spectroscopy (XPS). Our investigations provide mechanistic insight into the photoreduction kinetics from AuIII to AuI and then AuI to Au0. We unambiguously show that XPS photoreduction occurs in stepwise fashion via the AuI state. Both photoreduction steps undergo first-order kinetics.